A rapid method of heterologous gene cloning using cotransformation of lambda genomic DNA banks in Aspergillus nidulans - M. S. Stanley; P. Hooley; N. J.W. Clipson (Fungal Genetics Reports, 1995)
Relatively few fungal genera possess the extensive collections of mutants or reliable transformation systems that are found in favoured species such as Aspergillus nidulans, Saccharomyces cerevisiae or Neurospora crassa. Consequently, heterologous gene cloning protocols that circumvent the requirement for mutant construction or the development of transformation vectors in a previously uncharacterized species, are attractive. Lambda vectors probably provide the most versatile group of cloning vehicles but, with some exceptions (Pall and Brunelli 1994 Fungal Genet. Newsl. 41:63-65 ), they do not carry selectable markers for fungal transformation. Cooley et al (1990 Mycol. Res. 94:145-151) nevertheless demonstrated that lambda molecules could be cotransformed effectively into Septoria nodorum along with a conventional vector carrying a selectable marker. Here, we describe an extension of that protocol demonstrating that such cotransformed molecules can be rescued efficiently from Aspergillus nidulans as a host. Lambda genomic DNA libraries of other fungi may thus be screened by complementation of A. nidulans mutants. Additionally, the protocol offers a second method of gene bank screening via conventional plaque hybridization, so exploiting the large cloning capacity of lambda replacement vectors. Recently, we have cloned DNA capable of complementing the A. nidulans salt sensitivity mutation sltA1, (Spathas 1978 Aspergillus Newslett. 14:28), from the marine hyphomycete Dendryphiella salina, using this cotransformation approach.